Status and conservation of freshwater fauna (Zoological Records and Reviews, 2025)
Freshwater ecosystems harbour disproportionate biodiversity yet face the most severe and accelerating decline of anymajor biome globally. This study provides an integrated status assessment and conservation analysis of freshwaterfauna in three of Europe's most biologically distinct freshwater regions -- the Iberian Peninsula (Spain), the Seine-Loireriver system (France), and Scandinavia (Denmark and Sweden) -- using multi-taxon biodiversity surveys (fish,amphibians, macroinvertebrates, freshwater molluscs) at 96 river and lake sites, long-term population trend data fromnational monitoring programmes (1990-2024), and multi-stressor pressure indices. A total of 24,847 individual recordsacross 341 taxa were recorded. Freshwater biodiversity index (FBI) scores reveal that 60.4% of assessed river sites failEU Water Framework Directive (WFD) good ecological status for biological quality elements. Long-term trend analysisshows that 58.4% of assessed freshwater vertebrate species have declining 10-year population trends, led by freshwaterfish (72.4% declining) and amphibians (64.8% declining). Multi-stressor pressure index (MPI) was the strongest predictorof FBI (beta = -0.68 +- 0.08, p < 0.001), with hydrological alteration, nutrient pollution, and invasive species constitutingthe dominant pressure triad. Mediterranean freshwater sites (Spain) showed the most severe degradation (mean FBI38.4 +- 6.8 vs. Scandinavian reference 72.4 +- 8.4), driven by severe summer low-flow conditions exacerbated by climatechange and irrigation abstraction. Conservation gap analysis identifies 38 high-priority freshwater sites currently outsidethe Natura 2000 network requiring urgent designation for eight Annex II freshwater species. These findings provide theevidence base for WFD third River Basin Management Plan cycle priorities and EU Nature Restoration Law freshwaterrestoration targets.
Keywords: Natura 2000; conservation gaps; Scandinavia; Iberian Peninsula; population trends; multi-stressor; macroinvertebrates; freshwater fish; Water Framework Directive; freshwater biodiversity